A conceptual kano and quality function deployment (Qfd) framework for healthcare service - Razli Che Razak; Norshahrizan Nordin (2011)
Healthcare organization is struggling to provide customer driven quality service. The key success of healthcare service is the ability to develop a comprehensive healthcare service and deliver the best service direct to customer as required. Coherently, the measure of customer feedback should definitely show good perception of service fulfillment and satisfaction. As part of quality improvement process, an outstanding healthcare organization should practice an effective complaint management system (CMS) as the main voice of customer (VOC) source, which directly mirror the quality of healthcare service. The CMS will act as an essential decision support tool by providing seamless handling of complaints, introduces systematic improvement process, thus enabling hospitals to turn weakness into opportunities. However, Malaysian top public healthcare organizations are implicitly not really put much efforts to have a kind of proper CMS to treat complaints as critical and need immediate resolution. In other words, the VOC might not be heard in right way and account as the customer demand, expect and desire. This scenario may be the evident and reason why the present states of public Malaysian healthcare service providers are still unable to fully incorporate the customer requirement or complaint in to their strategic agendas, which account all the customer needs and expectations. This paper presents the current scenario of local public healthcare service with special focus to their implementation of CMS or similar system, in conjunction with healthcare constraints and VOC. Based on recent healthcare literature, an inclusive comparison is made and discussed to justify the gap of improvement in healthcare service. From findings, it is identified that complaint management practice is lacking of systematic procedure to prioritize complaints by customers. To be competitive, an alternative customer prioritizing approach mainly incorporates the Quality Function Deployment (QFD) and Kano’s Model is proposed conceptually. The new mechanism concept is hope to effectively address a complaint which not only satisfies the customer but also an opportunity to create positive experience with customers, building a healthier foundation, stronger brand value and avoiding legal penalties. It also provides fair balance information for decision making while facing constraints such as operational, legal, human resource and market pressures